2015
DOI: 10.1155/2015/617268
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Diverticular Perforation in a Young Patient with Rheumatoid Arthritis on Methotrexate

Abstract: Background. Disease-modifying antirheumatic drugs (DMARDs), such as methotrexate (MTX), are associated with gastrointestinal toxicity. MTX inhibits dihydrofolate reductase, but it is unclear if polymorphisms of the methylenetetrahydrofolate reductase (MTHFR) gene predict toxicity. Case. We describe a 33-year-old male with polyarticular rheumatoid arthritis who developed sigmoid diverticular perforation while receiving methotrexate, folic acid, prednisone, and naproxen. He tested heterozygous for the C677T alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A recent hypothesis regarding the association between disease-modifying antirheumatic drugs (DMARDs) and spontaneous diverticular perforation has been proposed in the literature, but a definitive association has not been established yet. A given example of this association is a case of a rheumatoid arthritis patient on methotrexate who had a spontaneous diverticular perforation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent hypothesis regarding the association between disease-modifying antirheumatic drugs (DMARDs) and spontaneous diverticular perforation has been proposed in the literature, but a definitive association has not been established yet. A given example of this association is a case of a rheumatoid arthritis patient on methotrexate who had a spontaneous diverticular perforation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been no previously reported cases with a similar presentation. A previously published report of a symptomatic case in a patient with rheumatoid arthritis attributed spontaneous diverticular perforation to the use of the disease-modifying antirheumatic drug (DMARD), methotrexate [11]. However, there have been no subsequent studies that have confirmed an association between the use of DMARDs and spontaneous diverticular perforation.…”
Section: Discussionmentioning
confidence: 99%